ANALISIS EMOSI TOKOH UTAMA DALAM NOVEL ORIGAMI HATI KARYA BOY CANDRA - Herlina Ovianti; Christanto Syam; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
by the interest of the researcher to find out the psychology of the main character. The thing emphasized in this study was devoted to the emotions of the main character. Emotion is an overflow of feelings someone is shown with behavior. In this research, the researcher examined the relationship between stimulus and response of an emotion based on her behavior.The problem of this research was about the psychology of the main character, especially the emotions of the character. This problem was divided into two sub-problems, namely (1) What are the positive emotions of the main character in the novel “Origami Hati” by Boy Candra? (2) What are the negative emotions of the main character in the novel “Origami Hati” by Boy Candra? (3) How do you plan to implement the results of this research in the study of literature in high school twelfth grade ood? The purpose of this study was to describe the positive and negative emotions of the main character from the novel “Origami Hati”. Key words: maincharacter, emotion, Origami Hati